Antifungal activity of farnesol incorporated in liposomes and associated with fluconazole. (November 2020) - Bezerra, Camila Fonseca; de Alencar Júnior, José Geraldo; de Lima Honorato, Rosilaine; dos Santos, Antonia Thassya Lucas; Pereira da Silva, Josefa Carolaine; Gusmão da Silva, Taís; Leal, Antonio Linkoln Alves Borges; Rocha, Janaína Esmeraldo; de Freitas, Thiago Sampaio; Tavares Vieira, Thiago Adler; Bezerra, Maria Clara Fonseca; Sales, Débora Lima; et al.
Highlights: Farnesol has an antifungal activity associated with inhibition of fungal dimorphism. The incorporation of farnesol into liposomes significantly increased this activity. The association of liposomal farnesol potentiated the action of fluconazole. Abstract: Candida infections represent a threat to human health. Candida albicans is the main causative agent of invasive candidiasis, especially in immunosuppressed patients. The emergence of resistant strains has required the development of new therapeutic strategies. In this context, the use of liposomes as drug carrier systems is a promising alternative in drug development. Thus, considering the evidence demonstrating that sesquiterpene farnesol is a bioactive compound with antifungal properties, this study evaluated the activity farnesol-containing liposomes against different Candida strains. The IC50 of farnesol and its liposomal formulation was assessed in vitro using cultures of Candida albicans, Candida tropicalis, and Candida krusei . The Minimum Fungicidal Concentration (MFC) was established by subculture in solid medium. The occurrence of fungal dimorphism was analyzed using optical microscopy. The effects on antifungal resistance to fluconazole were assessed by evaluating the impact of combined therapy on the growth of Candida strains. The characterization of liposomes was carried out considering their vesicular size, polydispersion index, and zeta medium potential, in addition to electron microscopy analysis. Farnesol exerted an antifungal activity that might be associated with the inhibition of fungal dimorphism, especially in Candida albicans . The incorporation of farnesol into liposomes significantly increased its antifungal activity against C. albicans, C. tropicalis, and C. krusei . In addition, liposomal farnesol potentiated the action of fluconazole against C. albicans and C. tropicalis . On the other hand, the association of unconjugated farnesol with fluconazole resulted in antagonistic effects. In conclusion, farnesol-containing liposomes have the potential to be used in antifungal drug development. However, further research is required to investigate how the antifungal properties of farnesol are affected by the interaction with liposomes, contributing to the modulation of antifungal resistance to conventional drugs.